Determinants of the Value Regional Government Financial Information Reports - Ridzal, Nining Asniar; Haliah, Haliah; Nirwana, Nirwana; Syamsuddin, Syamsuddin; Kusumawati, Andi (Journal of Applied Business Administration, 2024)
The purpose of this study is to directly demonstrate the factors influencing the financial report data value from local governments. The 32 regional apparatus organizations of the Baubau City government are the subjects of this study. 128 people participated in this study, including the financial treasurer, head of finance, secretary, and head of OPD. Questionnaires were employed in this study in order to gather data. The questionnaire in this study is measured using a Likert scale. Multiple linear regression analysis is the type of data analysis that was performed using the SPSS data processing software. This study employs quantitative methods. This research finds that the implementation of government accounting standards partially influences the value of financial report information. The information value of financial reports is influenced by the competence of human resources and how well the local government information system runs. Simultaneously, government accounting regulations, the quality of human resources, and local government information systems influence the information value of financial reports . . The implication of this research is that this research can fill gaps and provide useful information for local governments in increasing the value of financial report information